EXPERIMENTAL DESIGN TO TEST GAMIFICATION TOOLS ON STUDENT MOTIVATION AND PARTICIPATION (International Conference on Modern Science and Scientific Studies, 2025)
Increasing the motivation of students and ensuring their active participation in the educational process is always one of the important tasks. With the help of modern pedagogical technologies and innovative approaches, this goal can be achieved. In this context, the use of Game Tools serves as an effective tool in increasing the activity of students in the educational process and improving the quality of their mastering. This article will analyze in detail the essence of experimental design, its main stages and expected results, aimed at increasing the motivation and participation of students with the help of gaming tools.